2018
DOI: 10.3390/drones2030027
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Routing in Flying Ad-Hoc Networks Using Topology-Based Routing Protocols

Abstract: Abstract:The ever-increasing demand for flexible and portable communications has led to a rapid evolution in networking between unmanned aerial vehicles (UAVs) often referred to as flying ad-hoc networks (FANETs). However, due to the exclusive characteristics of UAVs such as high mobility, frequent topology change and 3D space movement, make routing a challenging task in FANETs. Due to these characteristics, designing new routing protocols for FANETs is quite difficult. In the literature study of FANETs, a var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
42
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(43 citation statements)
references
References 27 publications
0
42
0
1
Order By: Relevance
“…Additionally, frequent topology changes and 3D space movement make routing a tedious task in FANETs. To highlight this issue and understand the limits of routing in FANETs, Muhammad Asghar Khan et al [4] presented studied existing routing protocols for FANETs. The authors suggested that topology-based routing protocols are generally better than the other rival protocols in terms of throughput, end-to-end delay, and network load when applied to UAV ad hoc system.…”
mentioning
confidence: 99%
“…Additionally, frequent topology changes and 3D space movement make routing a tedious task in FANETs. To highlight this issue and understand the limits of routing in FANETs, Muhammad Asghar Khan et al [4] presented studied existing routing protocols for FANETs. The authors suggested that topology-based routing protocols are generally better than the other rival protocols in terms of throughput, end-to-end delay, and network load when applied to UAV ad hoc system.…”
mentioning
confidence: 99%
“…Table 1 summarizes papers conducting surveys on FANETs, covering various foci, which are self-explanatory given examples, as follows: Open issues, such as enhancing QoS and addressing the dynamicity of network topology. Axel et al [2] 2010 × × × Bauer et al [28] 2011 × × × × Neji et al [29] 2013 × × × × × Bekmezci et al [7] 2013 × × × × × × × × × Ozgur et al [18] 2013 × × × × × × Xie et al [30] 2014 × × × × × × Naser et al [31] 2016 × × × × × × × Gupta et al [32] 2016 × × × × × × × × [34] 2017 × × × × × × Omar et al [35] 2017 × × × × × × × × Zeeshan et al [36] 2018 × × × × × × Khan et al [37] 2018 × × × × × × × Antonio et al [38] 2018 × × × × × × Kaur et al [39] 2018 × × × × × × × Otto et al [40] 2018 × × × × × × × × Jinfang et al [41] 2018 × × × × × × Our paper 2019 × × × × × × × × × × × × × A cross × indicates that the option, which is represented by the column, applies to the reference, which is represented by the row.…”
Section: Our Contributionmentioning
confidence: 99%
“…To the best of our knowledge, this paper is the first of its kind to provide a comprehensive survey of routing schemes in FANETs, covering a diverse range of aspects. As shown in Table 1, surveys of routing schemes in FANETs have been conducted in the literature with a diverse range of foci [18,32,35,37,39,41], such as hierarchical and data centric approaches [18]; geographical location-based approaches [35]; as well as proactive, reactive, and hybrid routing schemes based on MANETs and VANETs [32]. In addition, although existing papers (see Table 1), including the surveys of routing schemes in FANETs, present taxonomies that categorize routing schemes and mobility models in FANETs, this paper presents a taxonomy that covers various aspects, including objectives, challenges, routing metrics, characteristics, and performance measures.…”
Section: Our Contributionmentioning
confidence: 99%
“…In addition, FANETs are deployed for highly sensitive applications that require reliable transmission, but the SDN-FANET could share the same wireless medium for data and control messages. Under these circumstances, to keep FANET's applications and services more reliable, stable, and active, it is essential to design an efficient and reliable control message transmission for FANET operations [19].It is essential to predict UAV information without control message transmission, reducing bandwidth consumption, and signaling overhead. For instance, based on mobility or energy consumption prediction algorithms, the controller can change the frequency control message dissemination.…”
mentioning
confidence: 99%
“…In addition, FANETs are deployed for highly sensitive applications that require reliable transmission, but the SDN-FANET could share the same wireless medium for data and control messages. Under these circumstances, to keep FANET's applications and services more reliable, stable, and active, it is essential to design an efficient and reliable control message transmission for FANET operations [19].…”
mentioning
confidence: 99%